The Inclusion of biomechanical principles when coaching handball to enhance performance in secondary school athletes in the Goromonzi District - Masara, Regis (BUSE, 2024)
Motivation and support are keys to success, they play a crucial role in setting the goals of secondary school sports. This study focuses on enhancing performance in handball athletes through the application of biomechanical principles among secondary schools in Goromonzi district secondary schools participated in the study. Eligible participants were given consent forms based on their availability at the stations, they were given questionnaires based on the study and were instructed on how to fill out the questionnaires so that they return them completed. At the next session, all questionnaires were received. while executing skills as they were instructed by their coaches during the training. Key factors affecting the performance of handball in secondary schools in the Goromonzi district might be a result of lack application of biomechanical principles, and limited access to resources and facilities. Based on these findings, confidence-building exercises an application of correct principles during the raining sessions will change their performance positively. The application of biomechanical principles can be an effective way to enhance performance among secondary school handball players in Goromonzi District. Practical recommendations from this research emphasize the application of the principles by coaches. There is a need to Future research should involve conducting studies in line with other sports to explore the positivity of application of biomechanical principles in handball among secondary school athletes.
Keywords: Biomechanical principles; Secondary school athletes; Athletes; SOCIAL SCIENCES::Social sciences::Social work::Sports research